Awareness of Social Presence on Virtual Fitness Platforms and Relationship with Exercise Motivation and Physical Activity Levels - Susannah Reiner; Michelle D’Abundo; Thomas Cappaert; Michael Miller (Physical Activity and Health, 2023)
The health benefits of physical activity are well-known, however, only 20% of the U.S. population meets the Physical Activity Guidelines for Americans. This study aimed to explore the association of awareness of social presence in a virtual fitness platform with motivation and physical activity levels (PAL). Virtual fitness users (n = 590, 42 ± 12.7 years old) completed the International Physical Activity Questionnaire and Behavioral Regulation of Exercise Questionnaire. Relative autonomy was correlated with PAL (r = .21, p < .001, 95.00% CI = [.13, .29]) and predicted PAL (F(1,588) = 27.03, p < .001). Awareness of social presence was significantly related to motivation (U = 41864.5, z = –5.99, p < .001), and predictive of relative autonomy (F(1,588) = 27.03, p < .001). The results suggest that higher relative autonomy is associated with higher PAL in virtual fitness users. Awareness of social presence on virtual platform appears to correlate to higher levels of relative autonomy, which may influence exercise adherence.